Difference between revisions of "009C Sample Midterm 2, Problem 1"

From Math Wiki
Jump to navigation Jump to search
(Replaced content with "<span class="exam">Evaluate: <span class="exam">(a)  <math>\lim _{n\rightarrow \infty} \frac{1}{\big(\frac{n-4}{n}\big)^n}</math> <span class="exam">(b)  <math...")
 
(One intermediate revision by the same user not shown)
Line 4: Line 4:
  
 
<span class="exam">(b) &nbsp;<math>\sum_{n=1}^\infty \frac{1}{2} \bigg(\frac{1}{4}\bigg)^{n-1} </math>
 
<span class="exam">(b) &nbsp;<math>\sum_{n=1}^\infty \frac{1}{2} \bigg(\frac{1}{4}\bigg)^{n-1} </math>
 +
<hr>
 +
[[009C Sample Midterm 2, Problem 1 Solution|'''<u>Solution</u>''']]
  
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
+
[[009C Sample Midterm 2, Problem 1 Detailed Solution|'''<u>Detailed Solution</u>''']]
!Foundations: &nbsp;
 
|-
 
|'''1.''' '''L'Hôpital's Rule'''
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; Suppose that &nbsp;<math style="vertical-align: -11px">\lim_{x\rightarrow \infty} f(x)</math>&nbsp; and &nbsp;<math style="vertical-align: -11px">\lim_{x\rightarrow \infty} g(x)</math>&nbsp; are both zero or both &nbsp;<math style="vertical-align: -1px">\pm \infty .</math>
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; If &nbsp;<math style="vertical-align: -19px">\lim_{x\rightarrow \infty} \frac{f'(x)}{g'(x)}</math>&nbsp; is finite or &nbsp;<math style="vertical-align: -4px">\pm \infty ,</math>
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; then &nbsp;<math style="vertical-align: -19px">\lim_{x\rightarrow \infty} \frac{f(x)}{g(x)}\,=\,\lim_{x\rightarrow \infty} \frac{f'(x)}{g'(x)}.</math>
 
|-
 
|'''2.''' The sum of a convergent geometric series is &nbsp; <math>\frac{a}{1-r}</math>
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; where &nbsp;<math style="vertical-align: 0px">r</math>&nbsp; is the ratio of the geometric series
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; and &nbsp;<math style="vertical-align: 0px">a</math>&nbsp; is the first term of the series.
 
|}
 
  
  
'''Solution:'''
 
 
'''(a)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|Let
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{y} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg(\frac{n-4}{n}\bigg)^n}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} \bigg(1-\frac{4}{n}\bigg)^n.}
 
\end{array}</math>
 
|-
 
|We then take the natural log of both sides to get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\ln y = \ln\bigg(\lim_{n\rightarrow \infty} \bigg(1-\frac{4}{n}\bigg)^n\bigg).</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|We can interchange limits and continuous functions.
 
|-
 
|Therefore, we have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\ln y} & = & \displaystyle{\lim_{n\rightarrow \infty} \ln \bigg(1-\frac{4}{n}\bigg)^n}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} n\ln\bigg(1-\frac{4}{n}\bigg)}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} \frac{\ln \bigg(1-\frac{4}{n}\bigg)}{\frac{1}{n}}.}
 
\end{array}</math>
 
|-
 
|Now, this limit has the form &nbsp;<math style="vertical-align: -13px">\frac{0}{0}.</math>
 
|-
 
|Hence, we can use L'Hopital's Rule to calculate this limit.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|Now, we have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\ln y } & = & \displaystyle{\lim_{n\rightarrow \infty} \frac{\ln \bigg(1-\frac{4}{n}\bigg)}{\frac{1}{n}}}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow \infty} \frac{\ln \bigg(1-\frac{4}{x}\bigg)}{\frac{1}{x}}}\\
 
&&\\
 
& \overset{L'H}{=} & \displaystyle{\lim_{x\rightarrow \infty} \frac{\frac{1}{\big(1-\frac{4}{x}\big)}\frac{4}{x^2}}{\big(-\frac{1}{x^2}\big)}}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow \infty} \frac{-4x}{x-4}}\\
 
&&\\
 
& = & \displaystyle{-4.}
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 4: &nbsp;
 
|-
 
|Since &nbsp;<math>\ln y= -4,</math>&nbsp; we know
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>y=e^{-4}.</math>
 
|-
 
|Now, we have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\lim _{n\rightarrow \infty} \frac{1}{\big(\frac{n-4}{n}\big)^n}} & = & \displaystyle{\frac{\displaystyle{\lim_{n\rightarrow \infty} 1}}{\displaystyle{\lim_{n\rightarrow \infty} \bigg(\frac{n-4}{n}\bigg)^n}}}\\
 
&&\\
 
& = & \displaystyle{\frac{1}{e^{-4}}}\\
 
&&\\
 
& = & \displaystyle{e^4.}
 
\end{array}</math>
 
|}
 
 
'''(b)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we not that this is a geometric series with &nbsp;<math style="vertical-align: -14px">r=\frac{1}{4}.</math>
 
|-
 
|Since &nbsp;<math style="vertical-align: -14px">|r|=\frac{1}{4}<1,</math>
 
|-
 
|this series converges.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we need to find the sum of this series.
 
|-
 
|The first term of the series is &nbsp;<math style="vertical-align: -13px">a_1=\frac{1}{2}.</math>
 
|-
 
|Hence, the sum of the series is
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\frac{a_1}{1-r}} & = & \displaystyle{\frac{\frac{1}{2}}{1-\frac{1}{4}}}\\
 
&&\\
 
& = & \displaystyle{\frac{\big(\frac{1}{2}\big)}{\big(\frac{3}{4}\big)}}\\
 
&&\\
 
& = & \displaystyle{\frac{2}{3}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math style="vertical-align: -1px">e^{4}</math>
 
|-
 
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math style="vertical-align: -20px">\frac{2}{3}</math>
 
|}
 
 
[[009C_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009C_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 11:35, 12 November 2017

Evaluate:

(a)  

(b)  


Solution


Detailed Solution


Return to Sample Exam